ANTI-PERIODIC SOLUTIONS FOR FRACTIONAL-ORDER BIDIRECTIONAL ASSOCIATIVE MEMORY NEURAL NETWORKS WITH DELAYS - Tuz, Munevver; Suroglu, Gulden Altay (Vinca Inst Nuclear Sci, 2019)
This paper concerns fractional-order bidirectional associative memory neural networks with distributed delays. Based on inequality technique and Lyapunov functional method, some novel sufficient conditions are obtained for the existence and exponential stability of anti-periodic solutions are established. An example is given to show the feasibility main results.
Keywords: bidirectional associative memory neural networks; existence; fractional differential equation; global exponential stability; delays; anti-periodic